A new species of the ghost shrimp genus Andamancalliax Sakai, 2011 from Iran (Crustacea: Decapoda: Axiidea: Eucalliacidae) - Sepahvand, Vahid; Tudge, Christopher (Zootaxa, 2022)
A new species of eucalliacid ghost shrimp is described from the Gulf of Oman, Iran. Andamancalliax poorei sp. nov. is the first species of the genus described from Iranian subtidal waters and the third species worldwide. Andamancalliax poorei sp. nov. most resembles A. arafura Poore, 2021 from the Arafura Sea but can be differentiated by characters of the minor cheliped, maxilliped 3 and uropodal endopod.